Dr. Spock an American life - Maier, Thomas (Harcourt Brace, 1998)
Dr. Benjamin Spock is a uniquely American figure, a Connecticut Yankee whose name is a symbol of family life and whose Book of Baby and Child Care is revered for its common-sense, down-to-earth voice. At the same time, in many ways, Spock is a revolutionary and a magnet for controversy. The first pediatrician to apply Freud's theories of psychology to children, he wrote his book as a Freudian tract in disguise, intentionally camouflaging Freud for Americans (mixing in a little of John Dewey's progressive educational psychology as well as a great chunk of old-fashioned American optimism). When he applied his ideals to politics, Spock shocked his multitude of fans by protesting against the Vietnam War with Martin Luther King in 1967 and by running for president on the People's Party ticket in 1972. He was attacked by Norman Vincent Peale and Spiro Agnew for fostering a "permissive" society and by feminists for his traditional attitudes about women's role in the family. Perhaps even more startling, however, is Spock's troubled personal life. Thomas Maier's extensive interviews with Spock, his family, and those who knew him draw the first complete picture of this complicated man.
Keywords: Spock, Benjamin <1903-1998>; Spock, Benjamin -- 1903-1998; Kinderartsen; Pediatricians -- United States -- Biography; Pediatrics -- United States -- Biography; USA; Biografie